Comparative sustainability investigation on a novel industrial-waste-based soil stabilizer and cement based on life cycle assessment - Jiayi Luo; Feng Yu; Xin Chen; Shuaikang Li (Scientific Reports)
Abstract This study employed the Life Cycle Assessment (LCA) methodology to evaluate the environmental impacts of producing a new soil hardening agent. The hardening agent is made from industrial waste residues, combined with cement, and improved with polycarboxylate superplasticizers. A comprehensive input-output inventory of the production process was established, and the eFootprint software was employed to model and quantitatively analyze various environmental impact categories, including global warming potential (GWP), abiotic depletion potential (ADP), and human toxicity potential (HTP). The results were compared with the environmental impacts associated with Ordinary Portland Cement (OPC) production. An economic comparison between a novel hardening agent and conventional cement—spanning the entire process from raw material procurement to final product—was conducted to evaluate the total production cost. This analysis offers a financial rationale for the substitution of cement with industrial solid waste. Results from characterization, normalization, and sensitivity analyses reveal that, in the production process assessed using 1 ton of hardening agent as the functional unit, GWP emerges as the most dominant environmental impact category. Compared to the production of OPC, the industrial waste-based novel soil hardening agent demonstrates a reduction of 69.9% in total environmental impact, with a particularly pronounced advantage in mitigating GWP. From an economic perspective, the novel hardening agent demonstrates a 29.32% reduction in production cost compared to conventional cement. Therefore, the novel soil hardening agent synthesized from industrial solid waste as a primary raw material offers substantial advantages in terms of both environmental performance and economic feasibility, making it a promising alternative to conventional cement-based materials.